Immunotherapy in Penile Squamous Cell Carcinoma: Present or Future? Multi-Target Analysis of Programmed Cell Death Ligand 1 Expression and Microsatellite Instability - Montella, Marco; Sabetta, Rosalaura; Ronchi, Andrea; De Sio, Marco; Arcaniolo, Davide; De Vita, Ferdinando; Tirino, Giuseppe; Caputo, Alessandro; D’Antonio, Antonio; Fiorentino, Francesco; Facchini, Gaetano; Lauro, Giovanni Di; et al. (Frontiers in Medicine, 2022)
Background Penile cancer (PC) is an extremely rare malignancy, and the patients at advanced stages have currently limited treatment options with disappointing results. Immune checkpoint inhibitors anti-programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) are currently changing the treatment of several tumors. Furthermore, the microsatellite instability (MSI) and the deficient mismatch repair system (dMMR) proteins represent predictive biomarkers for response to immune checkpoint therapy. Until present, few data have been reported related to PD-L1 expression and MSI in PC. The main aim of our study was the evaluation of PD-L1 expression in tumor cells (TCs) and tumor-infiltrating lymphocytes (TILs) in immune cells and the analysis of dMMR/MSI status in a large series of PCs. Methods A series of 72 PC, including 65 usual squamous cell carcinoma (USCC), 1 verrucous, 4 basaloid, 1 warty, and 1 mixed (warty-basaloid), was collected. Immunohistochemistry (IHC) was performed to assess PD-L1 expression using two different anti-PD-L1 antibodies (clone SP263 and SP142 Ventana) and MMR proteins expression using anti-MLH1, anti-PMS2, anti-MSH2, and anti-MSH6 antibodies. PCR analysis was performed for the detection of MSI status. Results Of the 72 PC cases analyzed by IHC, 45 (62.5%) cases were TC positive and 57 (79%) cases were combined positive score (CPS) using PDL1 SP263. In our cohort, TILs were present in 62 out of 72 cases (86.1%), 47 (75.8%) out of 62 cases showed positivity to PDL1 clone SP142. In our series, 59 cases (82%) had pMMR, 12 cases (16.7%) had lo-paMMR, and only 1 case (1.3%) had MMR. PCR results showed that only one case lo-paMMR was MSI-H, and the case dMMR by IHC not confirmed MSI status. Conclusion Our findings showed that PD-L1 expression and MSI status represent frequent biological events in this tumor suggesting a rationale for a new frontier in the treatment of patients with PC based on the immune checkpoint inhibitors.